Ontological, Teleological and Methodological Support of Curriculum-Evaluation Models Applied in Venezuela's Field of Higher Education - Rosalina González López (Universidad Autónoma de Baja California, 2010)
Scientific and technological changes, low relevance of the educative programs and economic globalization, have lead to the resurgence of evaluation as an innovative tool. However, the initiatives show a lack of delimitation in their interpretative understanding, adopting diffuse conceptions of curriculum and its evaluation. Thus, the present study investigation was done to determine, through a content analysis using the classic method of Sanz (2004), how the curriculum models most usually applied in the country are sustained ontologically, teleologically and methodologically. The models are based on a quite uniform ontological and teleological concept of curriculum. On the other hand, methodologically they adopt three-dimensional models that include knowing, doing and being; incorporating elements of the multidirectional approach. In curricular evaluation, they demonstrate homogeneity in their ontology and teleology, but not in their methodology.